Robotics Workshop to Increase Motivation and Science Literacy of SMP IT Khairu Ummah Rejang Lebong Students - Mayub, Afrizal; Firdaus, M. Lutfi; Fahmizal, Fahmizal; Ruyani, Aceng; Lazfihma, Lazfihma; Dewi , Deshinta Arrova (CV Media Inti Teknologi, 2025)
This activity aims to Increase the Motivation and Science Literacy of SMP IT Khairu Ummah Rejang Lebong Students. This activity is one form of implementing the tridharma of higher education. One of the tri dharmas of higher education is community service, this service activity is an activity that every lecturer must carry out, therefore lecturers in the Master of Science program at Bengkulu University collaborated with IT SMP teacher Khairu Ummah Rejang Lebong Bengkulu on September 28, 2024, to carry out service activities at SMP IT Khairu Ummah Rejang Lebong. This collaboration takes the form of community service activities at SMP IT Khairu Ummah Rejang Lebong Bengkulu with the title